The Role of Flavonoids in GH and IGF-1 Signaling Pathways: A Systematic Review - Aisyah Latiefah; Reni Paramita; Linda Erlina; Dwirini Retno (International Journal of Science and Environment (IJSE), 2026)
Flavonoids are naturally occurring bioactive compounds widely found in fruits, vegetables, tea, and various medicinal plants. Numerous studies have demonstrated that flavonoids exhibit biological activities involved in the regulation of cell growth, metabolism, and aging processes through their effects on the growth hormone (GH) and insulin-like growth factor-1 (IGF-1) signaling axis. The GH/IGF-1 pathway plays a crucial role in growth regulation, cellular differentiation, energy metabolism, and the development of various diseases, including cancer and metabolic disorders. Therefore, understanding the interaction between flavonoids and this signaling pathway is essential for the development of natural product-based therapeutic strategies. This study employed a Systematic Literature Review (SLR) approach to identify, retrieve, and synthesize scientific evidence regarding the role of flavonoids in modulating the GH and IGF-1 signaling pathways. Literature searches were conducted across several international scientific databases following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Eligible articles were then qualitatively analyzed to evaluate the molecular mechanisms of flavonoids in the regulation of components within the GH/IGF-1 signaling pathway.The results indicate that various flavonoids, including quercetin, kaempferol, genistein, epigallocatechin gallate (EGCG), and luteolin, can modulate the GH/IGF-1 axis by regulating IGF-1 receptor expression and downstream signaling pathways such as PI3K/AKT/mTOR and MAPK. These mechanisms contribute to the regulation of cell proliferation, induction of apoptosis, reduction of oxidative stress, and improvement of metabolic homeostasis. Overall, these findings suggest that flavonoids hold potential as therapeutic and preventive agents in conditions associated with dysregulation of the GH/IGF-1 signaling pathway.